The scarecrows' wedding - Donaldson, Julia, 1948- (Scholastic Children's Books, 2015)
Betty O'Barley and Harry O'Hay invite you to... the best wedding ever, the best wedding yet, the wedding that no one will ever forget. But will wicked scarecrow, Reginald Rake, spoil their special day?